Ecocide as an Environmental Crime: Urgency for Legal Reform in Indonesia - Widiartana, Gregorius; Setyawan, Vincentius Patria; Anditya , Ariesta Wibisono (Journal of Law, Environmental and Justice, 2025)
The increasing frequency and scale of environmental destruction in Indonesia, such as deforestation, mining disasters, and pollution of vital ecosystems, reveal the inadequacy of existing environmental criminal law to address crimes with transboundary and long-term ecological impacts. While Indonesian law recognizes environmental violations, it does not yet criminalize ecocide—a grave act of environmental harm—either as an extraordinary crime or as an international offense. This paper aims to explore the urgency of incorporating ecocide as a distinct criminal category in Indonesia’s legal system by analyzing the legal gaps and limitations in current legislation, particularly Law No. 32 of 2009 on Environmental Protection and Management. Employing a normative juridical method with a comparative legal approach, the study examines developments in countries such as Belgium and France that have begun codifying ecocide, as well as international efforts to include ecocide under the Rome Statute. The research finds that the absence of ecocide in Indonesian criminal law limits the state’s ability to deter and prosecute large-scale environmental crimes effectively. It concludes that the criminalization of ecocide, both nationally and as part of global legal harmonization, is crucial to achieving ecological justice and long-term environmental protection in Indonesia.